Identification from Diverse Mammalian Poxviruses of Host-range Regulatory Genes Functioning Equivalently to Vaccinia Virus C7L - Meng, Xiangzhi (2007)
Vaccinia virus (VACV) C7L is a host-range gene that regulates cellular tropism of VACV. Distantly related C7L homologues are encoded by nearly all mammalian poxviruses, but whether they are host-range genes functioning similar to VACV C7L has not been determined. Here, we used VACV as a model system to analyze five different C7L homologues from diverse mammalian poxviruses for their abilities to regulate poxvirus cellular tropism. Three C7L homologues (myxoma virus M63R, M64R and cowpox virus 020), when expressed with an epitope tag and from a VACV mutant lacking the host-range genes K1L and C7L (vK1L(−)C7L(−)), failed to support productive viral replication in human and murine cells. In nonpermissive cells, these viruses did not synthesize viral late proteins, expressed a reduced level of the early protein E3L, and were defective at suppressing cellular PKR activation. In contrast, two other C7L homologues, myxoma virus (MYXV) M62R and Yaba-like disease virus (YLDV) 67R, when expressed with an epitope tag and from vK1L(−)C7L(−), supported normal viral replication in human and murine cells and restored the ability of the virus to suppress PKR activation. Furthermore, M62R rescued the defect of vK1L(−)C7L(−) at replicating and disseminating in mice following intranasal inoculation. These results show that MYXV M62R and YLDV 67R function equivalently to C7L at supporting VACV replication in mammalian hosts and suggest that a C7L-like host-range gene is essential for the replication of many mammalian poxviruses in mammalian hosts.